Perception of professional skills acquired in online learning among electronic engineering students - Nestor Alvarado-Bravo; Salvador Trujillo-Perez; Florcita Aldana-Trejo; Juan Antón-De Los Santos; Marco Anton-De Los Santos; Alejandro Paredes-Soria; Vidalina Chaccara-Contreras; Víctor Villanueva-Acosta; Madison Huarcaya-Godoy; Katherine Rodríguez-Zevallos (Institute of Advanced Engineering and Science, 2022)
The article aims to analyze the perception of professional skills acquired in online learning among electronic engineering students. The research method is qualitative, with a descriptive approach, since it focuses on analyzing the statistics of the students' perception (frequency of satisfaction levels). Initially, the reliability of the instrument was determined using Cronbach's Alpha, obtaining a consistency coefficient of 0.967 and 0.932, in the academic semesters 2020-I and 2020-II, respectively. The data collected by means of a virtual questionnaire were processed in the SPSS software transformed into the Likert scale. The results obtained show a high perception among electronic engineering students in reference to the professional skills they have acquired. There is an increase in satisfaction from 66.78% (2020-I) to 74.26% (2020-II) between the first and second academic semester, despite the abrupt and unexpected change in the teaching-learning modality, in the second semester achieved a greater adaptation of this process. However, the online learning method should continue to be improved so that students perceive with greater satisfaction that they possess the skills to solve problems and cases related to the specialty) and the skills to master practical professional skills.